2023
DOI: 10.1161/circulationaha.123.065748
|View full text |Cite
|
Sign up to set email alerts
|

Blinded Withdrawal of Long-Term Randomized Treatment With Empagliflozin or Placebo in Patients With Heart Failure

Milton Packer,
Javed Butler,
Cordula Zeller
et al.

Abstract: BACKGROUND: It is not known whether the benefits of sodium-glucose cotransporter 2 inhibitors in heart failure persist after years of therapy. METHODS: In the EMPEROR-Reduced (Empagliflozin Outcome Trials in Chronic Heart Failure With Reduced Ejection Fraction) and EMPEROR-Preserved (Empagliflozin Outcome Trials in Chronic Heart Failure With Preserved Ejection Fraction) trials, patients with heart failure were randomly assigned (double-blind) to placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In the additional trial after the end of the EMPEROR-Reduced and the EMPEROR-Preserved trials, patients withdrawn from treatment with empagliflozin showed an increased risk of HF events and worsening health status compared with patients withdrawn from the placebo [ 6 ]. Although the results of this trial indicate that the cessation of SGLT2i treatment may have deleterious consequences, some patients are unable to continue SGLT2i due to adverse events or chronic disease [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the additional trial after the end of the EMPEROR-Reduced and the EMPEROR-Preserved trials, patients withdrawn from treatment with empagliflozin showed an increased risk of HF events and worsening health status compared with patients withdrawn from the placebo [ 6 ]. Although the results of this trial indicate that the cessation of SGLT2i treatment may have deleterious consequences, some patients are unable to continue SGLT2i due to adverse events or chronic disease [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent RCT demonstrated that the risk of cardiovascular death or hospitalization for HF increased in patients withdrawn from empagliflozin [ 6 ]. This finding suggested a chronic effect of SGLT2i in patients with HF even after years of treatment, which dissipated after withdrawal of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium–glucose cotransporter 2 inhibitors (SGLT2‐I) should be used across the entire spectrum of left ventricular ejection fraction as a disease‐modifying drug, rather independent of congestion status. Importantly, continuation of SGLT2‐I should be emphasized as even short‐term withdrawal is associated with a worse outcome as evidenced by a recent analysis of the EMPEROR trials 13 . Loop diuretics remain the cornerstone for alleviating volume overload.…”
Section: Figurementioning
confidence: 99%
“…Importantly, continuation of SGLT2-I should be emphasized as even short-term withdrawal is associated with a worse outcome as evidenced by a recent analysis of the EMPEROR trials. 13 Loop diuretics remain the cornerstone for alleviating volume overload. True loop diuretic resistance is perhaps less frequent than historically thought.…”
mentioning
confidence: 99%